Feed efficiency in swine: A survey of current knowledge - J R Flohr; J F Patience; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2012)
Pork producers and advisers to the swine industry were surveyed about their knowledge of feed efficiency. The questionnaire was designed to accomplish three objectives: (a) determine the level of knowledge related to feed efficiency topics, (b) identify production practices being used that influence feed efficiency, and (c) identify information gaps or areas requiring additional knowledge to further improve feed efficiency. Producer responses imply that they are unfamiliar with information behind the effects of fat inclusion, particle size reduction, feed additives, and thermal environment on feed efficiency. Many were not sure which energy system to use for evaluating dietary energy. Consultants and individuals in academia had the highest percentage of correct answers for the knowledge questions, but less than half identified the correct response when asked how reducing particle size affects feed efficiency, and very few correctly answered the question on how thermal environment affects feed efficiency. This result suggests the need for more information and education in these two topic areas.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; Feed efficiency; Swine survey; Swine Industry